Fiber-Specific Differences in Protein Content of Pathways Related to mtorc1 Signaling and Oxidative Metabolism in Individuals with Obesity - Morales-Acuna, F (Nature Research, 2025)
This study aimed to compare the protein content of pathways related to mTORC1 signaling and oxidative metabolism in whole skeletal muscle and isolated muscle fibers from healthy individuals (HEALTHY) and individuals with obesity (OBESE). Muscle biopsies were obtained from 18 individuals. Samples were freeze-dried, and fibers were isolated and fiber-typed for type I and IIa myosin heavy chain isoforms. The protein content of Akt-1, mTOR, p70s6K, S6 ribosomal protein (S6RP), ERK1/2, p38, total protein ubiquitination (TPU), and OXPHOS proteins in whole muscle and isolated fibers was determined using immunoblotting. Muscle fiber morphology was also assessed. Fiber type proportion was similar in HEALTHY, while OBESE showed a greater proportion of type IIa fibers. Fiber cross-sectional area (CSA) was similar in HEALTHY, while OBESE showed greater CSA of type I fibers. Protein content of p70s6K was lower (73%, p = 0.008), while ERK1/2 (29%, p = 0.05) and TPU (32%, p = 0.03) were increased in whole muscle from OBESE compared with HEALTHY. Fiber-specific differences were found in p38 (IIa > I, p = 0.03) in HEALTHY, while OBESE showed different complex II and V (I > IIa, p = 0.03 and p = 0.04, respectively) between fibers. Furthermore, a negative correlation was found between body mass and p70s6K protein content. Our findings suggest that obesity impairs the mTORC1-related protein pathway while increasing degradation in individuals with obesity. © The Author(s) 2025.
Keywords: Skeletal muscle; Muscle ubiquitination; Muscle protein synthesis; Mitochondrial complex; Overweight